IDENTIFIKASI PENGETAHUAN METAKOGNISI CALON GURU FISIKA - Hera Novia; Ida Kaniawati; Dadi Rusdiana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The term â€œmetacognitionâ€ is defined as the ability of individuals to reflect, understand, and control their own thinking, learning and acting. Metacognition clasified to metacognitive knowledge and metacognitive regulation. Metacognitive knowledge consist of declaration knowledge, procedural knowledge, and conditional knowledge that refers to acquire knowledge about cognitive processes, knowledge that can be used to control their cognitive processes. The purpose of this article is to identified the metacognition knowledge of Physics Pre-Service Teacher. Six student in Solid State Physics lecture fulfill questionnaire and followed by interview. The analysis of questionnaire and interview data showed that the metacognition knowledge is still low, they could not describe about their purpose, only few of them could describe how they think, confuse what they shoud do to do the task. They only think that strategy is needed when they find difficulty and not sure with their ability to do the task. Key words: metacognitive knowledge, declarative, procedural, conditional.